(untitled) (Letters in Nonlinear Analysis and its Applications, 2025)
In this paper, we obtain some fixed point results involving α-admissibility for multi-valued F-contractions in the framework of complete S-metric spaces. Appropriate illustrations are provided to support the main results. Finally, an application is developed by demonstrating the existence of a solution to an integral equation. Also, as an application, we establish the existence and uniqueness of the solutions to differential equations in the framework of fractional derivatives involving Mittag-Leffler kernals via the fixed point technique. Our results extend and generalize many well-known results in the existing literature.